User-Centered Feature Prioritization in Stroke Self-Care Applications: A Kano Model Study - Winny Setyonugroho; Attar Husna Fathiya; Moch Zihad Islami; Fandi Setiawan; Sentagi Sesotya Utami; Musa Abdul Rahman; Iman Permana (Journal of Innovation Information Technology and Application (JINITA), 2026)
Stroke survivors often require ongoing support for long-term recovery, yet many face limited access to healthcare, particularly in developing countries like Indonesia. Mobile health technology enables supporting self-care. However, their usefulness and effectiveness depend heavily on their suitability to user needs. This study aims to identify and prioritize user-centered features in self-care apps for stroke survivors using the Kano Model. A questionnaire was distributed to 66 stroke survivors across Indonesia; after data filtering, 37 valid responses were analyzed using basic categorization, mean average scoring, and the Better-Worse method. Features were classified into Performance and Attractive categories and ranked by R-value, which measures sensitivity to user satisfaction. The highest-ranked Performance features were prevention of stroke recurrence (R = 1.03), emergency alert/warning system (R = 1.01), first aid handling (R = 0.97), and daily health data monitoring (R = 0.97). In the Attractive category, speech therapy (R = 0.93), notification reminders (R = 0.91), and online doctor consultation (R = 0.86) were top priorities. Features like font size adjustment (R = 0.70), voice commands (R = 0.70), and dark/light mode (R = 0.66) were lower in priority. These findings provide clear guidance for developing user-centered mobile applications that meet stroke survivors’ most valued needs.